Low Carbon Freight Services Analysis: A Review Study - Shahla Deris; Suhaiza Zailani; Md. Mamun Habib; Mohammad Reza Mansournia (International Journal of Supply Chain Management, 2017)
ABSTRACT_ The analysis of Low Carbon Freight Services is relatively recent. However, the topic has become one of the most popular in freight services research literature. A review of 80 Low Carbon Freight Services papers, published in the literature during the period 1995-2015, was undertaken to provide Freight Services researchers with a reference guide to the context, method and focus of previous studies. The outcome of these papers show there is some benefits to employ low carbon freight logistic include Economic benefits, Environmental benefits, Operational benefits and Intangible benefits. The study describes opportunities and contributions in relation to an increase in a competitiveness and flexibility of enterprise and all of participating supply chain segments.